Effect of Canopy Microclimate, Season and Region on Sauvignon blanc Grape Composition and Wine Quality - Marais, J.; Hunter, J.J.; Haasbroek, P.D. (South African Journal of Enology and Viticulture, 2017)
The effect of canopy microclimate on the grape aroma composition and wine quality of Sauvignon blanc was investigated in three climatically-different regions, i.e. in the Stellenbosch (1996 and 1997 season), Robertson and Elgin regions (1997 and 1998 season). A canopy shade treatment altering microclimate in a natural way, was applied to Sauvignon blanc vineyards in the three regions. Control vines were not manipulated. The concentrations of aroma compounds in the grapes, namely monoterpenes, Cu-norisoprenoids and 2-methoxy-3-isobutylpyrazine, were determined weekly during the respective ripening periods. Solar radiation above and within the canopies as well as temperature within the canopies were also measured continually during the ripening periods. The highest canopy solar radiation, temperature, and monoterpene and C13-norisoprenoid concentrations were found for the control treatments, followed by the shaded treatments. An opposite tendency was found for 2-methoxy-3-isobutylpyrazine, which is one of the most important components responsible for the typical green pepper/asparagus aroma of Sauvignon blanc. There appears to be a relationship between chemical and microclimatic data in each region and over seasons. Marked temperature and aroma component concentration differences were observed among the three regions during the cool 1997 season, which manifested in wine aroma parameters such as fruitiness and vegetative/asparagus/green pepper nuances. Two definite wine styles emerged, namely the green pepper/asparagus "cool climate" style and the "warm climate" fruity/tropical style. However, differences in 2-methoxy-3-isobutylpyrazine and C13-norisoprenoid levels and wine characteristics between regions were not as pronounced during the warm 1998 season. The data contribute to establishing guidelines for canopy manipulation for obtaining a specific wine character and quality. The choice lies with the viticulturist and winemaker to strive for and obtain, within limits, the style that they prefer.